Water Requirements, Water Distribution Pattern and Potassium Substitution with Sodium from Seawater for Pineapple Cultivation on Bris Soil - Md. Niazuddin, (2007)
Pineapple is one of the most traded tropical fruit in Malaysia; mostly planted on peat soil. However, Malaysia has a vast area of sandy fallow beach ridges interspersed swales (BRIS) soil. Due to lack of cultivable land, increasing populations, and urge to improve the standard of living of inhabitants of in this area, there is a need to develop a viable commercial-oriented agriculture. Therefore, the objectives of the study were to estimate the crop water requirements, water distribution patterns, and K substitution with Na from seawater for cultivation of pineapple on BRIS soil. A series of experiments including soil temperature, water distribution, and crop water requirements of the BRIS soil were determined in the glasshouse and field. Water distribution patterns were determined using water application rates of 2, 4, and 8 l/h emitters at different times of duration using a specially designed apparatus. Crop water requirements of „N-36‟ of pineapple were estimated by planting of different stages of plants on the lysimeters and using the CROPWAT model. Pineapple stages were adjusted according to their length of growth on the lysimeters and in the model. The estimated crop water requirements was applied in the field at BRIS soil area,Terengganu using Na from seawater for substitution of K requirements of pineapple (based on 300 kg K ha-1) at 15, 30, and 60% in comparison to the control (100% K) using fertigation techniques for 4 months with irrigation water. Pineapple growth, development, and yield were measured. With the exception in the morning, the topsoil temperature of BRIS soil was higher than the subsoil. The temperature gradually increased from 08:00 up to 14:00 hr of a day then decreased. On normal soil temperature and heated soil, the shape of water distribution of the wetted fronts was spherical or ellipsoidal. The higher discharge rate in short duration, the lateral movement was more as compared with the vertical movement. But the opposite was observed when lower discharge rate was applied in long time of duration. Wetted waterfronts were increased with increasing soil temperature in both horizontal and vertical directions. The average calculated crops reference evaporation (ETc) at the respective stages was 0.83, 0.73, 0.68 and 0.61 mm/day. The calculated average ETo was 1.99 mm/day. The estimated pineapple crop coefficient (Kc) value (0.50) was the highest at the early growing stage 1 because of the maximum ETc occurred from the bare soil and young pineapple with limited transpiration rate. The Kc value for pineapple was 0.30 at stage 2 to 4. The average depth of fertigation in the field using CROPWAT model was 1.67 mm/day. Application of 0, 15 and 30% Na from seawater substitution for K on plant height, number of leaf per plant, D-leaf length, and area, fresh and dry weight was not significantly different. Fruit length, diameter, and weight obtained from Na application at 15, and 30% Na for K substitution were not significantly different from 0% Na (100% K) treatment. The results indicate that up to 30% of pineapple K requirement can be substituted by Na obtained from seawater. Knowing the emitter size and soil water movement could ensure precise placement of water and nutrients in the active roots zone.